Bilateral simultaneous VATS for complete resection of bilateral posterior mediastinal bronchogenic cyst: A case report. (2016) - Amore, Dario; Cerqua, Francesco S.; Perrotta, Fabio; Cennamo, Antonio; Curcio, Carlo
Highlights: We report a case of 17 years-old male suffering from bronchogenic cysts of the mediastinum. A complete surgical resection was performed by using bilateral simultaneous VATS with three-port access. No intra and post-operative complications occurred. Abstract: Introduction: The mediastinal bronchogenic cysts represents 50%–60% of mediastinal cysts and rarely occurs in the posterior mediastinum. The final surgical resection is indicated for symptomatic patients and is recommended for some asymptomatic patients in order to establish the diagnosis and to avoid any subsequent complications. Case presentation: We report a case of 17 years-old male suffering from bronchogenic cysts of the mediastinum. The patient was admitted to our hospital complaining with dry chough and dyspnea; CT scan showed a cystic mass in posterior mediastinum. To achieve a correct diagnosis and to prevent the risk of complications, a complete surgical resection was performed by using bilateral simultaneous VATS. Discussion: Bronchogenic cysts manifest as solitary or multiple lesions, majority of which are located in the mediastinum while sometimes can occur in the lung parenchyma. They are usually asymptomatic and casually discovered at chest X-ray or CT scan. The most common complications are infections, pneumothorax and hemoptysis. The complete surgical resection is the only radical and definitive treatment of the bronchogenic mediastinal cysts. VATS permits good exposure of the thoracic cavity including the mediastinum and better evaluation of the anatomic relationship. The absence of intra and postoperative complications, the reduction of pain in the early postoperative period demonstrate the security of this approach. Conclusion: Bilateral simultaneous VATS for resection of bilateral posterior mediastinal bronchogenic cyst may be a useful approach. In our case no intra and post-operative complications occurred and patient discharged home on 4 rd day.